Pengaturan Judi Online dan Penegakan Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik (International Forum of Researchers and Lecturers, 2025)
Along with the advancement of technology, online gambling games that were initially only considered entertainment, turned into a source of income or known as online gambling. On this basis, the government issued Law Number 11 of 2008 concerning Information and Electronic Transactions to regulate the management of information and electronic transactions in Indonesia. Since its enactment in 2008, Law No. 11 of 2008 has not undergone major changes to keep pace with the rapid advancement of information technology, especially related to online gambling. This research is a normative judicial research supported by a legislative approach, a sociolegal approach and a conceptual approach using primary legal materials, secondary legal materials and tertiary legal materials. This study uses data collection techniques in the form of observation and literature studies. The processing technique of legal materials is carried out in several stages, namely inventory, classification, systematization and verification, after which it will be analyzed qualitatively judicially according to the information obtained from various legal materials. The results of this study show that (1) Regulation of online gambling in Indonesia is regulated in 9 laws and regulations, namely in laws and regulations (2) Law enforcement against online gambling in Indonesia has not been running effectively, seeing that the data on online gambling cases from year to year online gambling cases are increasing. (3) Legal protection for people involved in online gambling, having legal protection rights guaranteed by Law Number 8 of 1981 concerning the Criminal Procedure Law (KUHAP).